From Rural Roots to Urban Centers: The Transformation of Filipino Traditional Practices - Datu, Apolinar; Abubakar, Abdullah; Bacolod, Minsoware; Platon, Joseph; Cruz, Reine Joshua (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the evolving landscape of Filipino traditional practices in the context of urbanization, modernization, and globalization. Drawing responses from 100 participants across urban and rural settings, the research examined factors influencing the transformation of traditions, perceptions of younger generations, and the adaptations of cultural practices in cities. Findings revealed that technology and media, globalization, and economic pressures are the most significant drivers of change, with weighted means exceeding 4.30. Younger respondents were perceived as less engaged with traditions, often viewing them as outdated, although schools and communities were acknowledged as vital in sustaining cultural participation. Urban adaptations included modifying celebrations to fit modern schedules, simplifying practices to conserve resources, and utilizing social media to reimagine cultural expressions. Despite these shifts, deeply rooted traditions, particularly religious rituals and traditional cuisine—remain resilient symbols of cultural identity. Respondents envisioned Filipino traditions as increasingly adapted and modernized, often blending with global influences while retaining their essence. The study concludes that Filipino traditions are not being lost but rather reinterpreted to remain relevant. Recommendations highlight the roles of education, community initiatives, technology, and policy in preserving cultural heritage for future generations.